Development of the Performance of the Upper Limb module for Duchenne muscular dystrophy. (1st August 2013) - Mayhew, Anna; Mazzone, Elena S; Eagle, Michelle; Duong, Tina; Ash, Maria; Decostre, Valerie; Vandenhauwe, Marlene; Klingels, Katrijn; Florence, Julaine; Main, Marion; Bianco, Flaviana; Henrikson, Erik; et al.
<x xml:space="preserve">Abstract</x> Aim An international Clinical Outcomes Group consisting of clinicians, scientists, patient advocacy groups, and industries identified a need for a scale to measure motor performance of the upper limb. We report the steps leading to the development of the Performance of the Upper Limb (PUL), a tool specifically designed for assessing upper limb function in ambulant and non‐ambulant patients with Duchenne muscular dystrophy (DMD). Method The development of the PUL followed a number of steps, from the systematic review and a preliminary study exploring the suitability of the existing measures, to the application of a pilot version in a multicentric setting, with Rasch analysis of the preliminary results, leading to a revised pro forma. Results The PUL was specifically designed for DMD, with a conceptual framework reflecting the progression of weakness and natural history of functional decline in DMD. Modern psychometric methods were used to create a scale with robust internal reliability, validity, and hierarchical scalability; males with DMD and their families were involved iteratively throughout the process of the clinician‐reported outcome assessment tool development to establish clinical meaningfulness and relevance of individual PUL items to activities of daily living. Interpretation The module was developed using innovative approaches and will be useful for designing clinical trials.